Amino-borane oligomers bound to a Rh(I) metal fragment. - Dallanegra, R; Chaplin, AB; Tsim, J; Weller, A (2010)
Coordination complexes of previously observed intermediates, H(3)B.NMe(2)BH(2).NMe(2)H and [H(2)BNMeH](3), in the transition metal catalysed dehydrocoupling of H(3)B.NMe(2)H and H(3)B.NMeH(2) have been isolated and structurally characterised using the [Rh{PR'(2)(eta(2)-C(5)H(7))}](+) fragment. Their onward reactivity shows that further dehydrogenation is not a simple intramolecular process.